Responses of the aleppo pine (Pinus halepensis Mill.) and the holm oak (Quercus ilex L. subsp. ballota (Desf.) Samp.) to the collection of overland runoffs through minicatchments in different Mediterranean environments - DE SIMÓN NAVARRETE, E.; Ripoll Morales, M. A.; Fernández Ondoño, E.; Navarro Reyes, F. B.; Jiménez Morales, M. N.; Gallego Teruel, E. (Forest Systems; Vol 15, No 2 (2006), 2008)
Water is one of the most limiting factors in the forestation of Mediterranean areas, so that the survival and development of these areas is always connected to the availability of water resources. The aim of this study is to assess the efficiency of a series of hydraulic structures linked to land preparation, called minicatchments, as runoff collectors meant to increase water availability in the forestation. In order to do so, the amount of overland runoff reaching every seedling, as well as the survival of the reforestation in four places with different climatic and edaphic characteristics have been assessed. Results obtained show how water availability depends both on the amount of water reaching the bank and on the physical properties of the land. The areas that have normally been considered more difficult to restore due to a de-structured profile, to the presence of superficial physical crusts and to a scarce vegetal cover are the ones showing a better response to the technique of runoff collection trough minicatchments.
Keywords: minicatchment; overland runoff; Soil moisture